In-situ acoustic detection of critical heat flux for controlling thermal runaway in boiling systems. (August 2019) - Nishant Ranjan Sinha, Kumar; Ranjan, Durgesh; Raza, Md. Qaisar; Kumar, Nirbhay; Kaner, Swapnil; Thakur, Atul; Raj, Rishi
Highlights: We perform in-situ acoustic detection and feedback control of boiling crisis. Frequency spectrum of audible sound is explored across boiling regimes. A unique and previously unreported shift in the peak frequency is noted at CHF. A feedback controller is designed to detect CHF and power down the system. Control strategy minimizes thermal runaway for safe operations of boiling systems. Abstract: Heat transfer deteriorates and thermal runaway is observed due to the formation of a vapor blanket during boiling crisis. Such temperature excursions are undesired in practical applications and may cause device failure. Inherent complexities and the associated uncertainties with boiling systems have not allowed development of robust critical heat flux (CHF) prediction tools. Hence, a high factor of safety is adopted, limiting the practical application of boiling to low heat flux nucleate boiling regime only. Here we identify a unique feature in audible acoustic emissions wherein a sudden shift in peak frequency from ≈ 200 - 250 H z in the nucleate boiling regime to ≈ 400 - 500 H z is observed at CHF. We show that a simple threshold-based feedback control strategy with a threshold frequency can be used to accurately detect the CHF and turn off the system to minimize thermal runaway. We show that the control strategy is equally robust on smooth and nanostructured copper surfaces. We believe that the ability to detect CHF and then power down the system within one second avoids transition to the undesired film boiling regime and is critical for safety and reliability of boiling-based systems and devices.